Validation of the peak bilirubin criterion for outcome after partial hepatectomy. Issue 10 (October 2016) - van Mierlo, Kim M.C.; Lodewick, Toine M.; Dhar, Dipok K.; van Woerden, Victor; Kurstjens, Ralph; Schaap, Frank G.; van Dam, Ronald M.; Vyas, Soumil; Malagó, Massimo; Dejong, Cornelis H.C.; Olde Damink, Steven W.M.
Abstract: Introduction: Postoperative liver failure (PLF) is a dreaded complication after partial hepatectomy. The peak bilirubin criterion (>7.0 mg/dL or ≥120 μmol/L) is used to define PLF. This study aimed to validate the peak bilirubin criterion as postoperative risk indicator for 90-day liver-related mortality. Methods: Characteristics of 956 consecutive patients who underwent partial hepatectomy at the Maastricht University Medical Centre or Royal Free London between 2005 and 2012 were analyzed by uni- and multivariable analyses with odds ratios (OR) and 95% confidence intervals (95%CI). Results: Thirty-five patients (3.7%) met the postoperative peak bilirubin criterion at median day 19 with a median bilirubin level of 183 [121–588] μmol/L. Sensitivity and specificity for liver-related mortality after major hepatectomy were 41.2% and 94.6%, respectively. The positive predictive value was 22.6%. Predictors of liver-related mortality were the peak bilirubin criterion (p < 0.001, OR = 15.9 [95%CI 5.2–48.7]), moderate-severe steatosis and fibrosis (p = 0.013, OR = 8.5 [95%CI 1.6–46.6]), ASA 3–4 (p = 0.047, OR = 3.0 [95%CI 1.0–8.8]) and age (p = 0.044, OR = 1.1 [95%CI 1.0–1.1]). Conclusion: The peak bilirubin criterion has a low sensitivity and positive predictive value for 90-day liver-related mortality after major hepatectomy.